2016
DOI: 10.4172/2332-2543.1000170
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Indiscriminate Disposal of Waste: A Case Study of the Keta Lagoon in the Volta Region of Ghana

Abstract: Over the years, the issue of waste generation and management have been a major issue of concern, stemming a number of countries around the world, thus, developing countries. The ultimate aim of this study was to investigate into the effects of indiscriminate disposal of waste in and around the Keta Lagoon in the Volta region of Ghana. The study highlighted quite a number of respondents, who had lived in the area for quite a lengthy period and had observed the changes with regards to rapid deteriorating conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…The quote is consistent with Ahmed and Isaac's [ 5 ] finding that some of the consequences of improper waste disposal in and around the Keta Lagoon in Ghana were water and air pollution, floods, and health issues. It is clear from the pieces of evidence that all categories of respondents were aware that poor waste disposal practices had negative implications for public and environmental health.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The quote is consistent with Ahmed and Isaac's [ 5 ] finding that some of the consequences of improper waste disposal in and around the Keta Lagoon in Ghana were water and air pollution, floods, and health issues. It is clear from the pieces of evidence that all categories of respondents were aware that poor waste disposal practices had negative implications for public and environmental health.…”
Section: Resultssupporting
confidence: 87%
“…The finding that improper waste disposal practices could impede navigation corroborated that of Ahmed and Isaac [ 5 ]. According to Ahmed and Isaac, fisherfolk in the Keta community in Ghana reported that waste in the Keta Lagoon was creating navigational challenges for the fishermen.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations